2018
DOI: 10.1002/cncr.31519
|View full text |Cite
|
Sign up to set email alerts
|

Results of the AHOD0431 trial of response adapted therapy and a salvage strategy for limited stage, classical Hodgkin lymphoma: A report from the Children's Oncology Group

Abstract: This limited chemotherapy response-based approach was successful in patients who had a negative PET1 result, had MC histology, or had a low red blood cell sedimentation rate. In this treatment paradigm, evaluation of increased chemotherapy intensity or the integration of active new agents is indicated for patients who have nodular sclerosis histology with a high ESR or who have a positive PET1 result. Cancer 2018. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 16 publications
(40 reference statements)
1
43
2
Order By: Relevance
“…For the low-risk group, prospective studies have reported an excellent survival with low-dose IFRT [ 9 , 10 , 19 ]. There is controversy about the necessity of RT for patients with a good response after initial chemotherapy, with concerns about balancing disease control with the risk of long-term toxicities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the low-risk group, prospective studies have reported an excellent survival with low-dose IFRT [ 9 , 10 , 19 ]. There is controversy about the necessity of RT for patients with a good response after initial chemotherapy, with concerns about balancing disease control with the risk of long-term toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients in our study received heterogeneous treatment because of the long duration of the case collection period and the development of the riskbased chemotherapy regimen. For the low-risk group, prospective studies have reported an excellent survival with low-dose IFRT [9,10,19]. There is controversy about the necessity of RT for patients with a good response after initial chemotherapy, with concerns about balancing disease control with the risk of long-term toxicities.…”
Section: Variablementioning
confidence: 99%
“…A comprehensive review in 2015 summarized contemporary paediatric treatment approaches for de novo HL (Kelly, ). Five‐year DFS in paediatric HL ranged from 79·8% to 97% for low risk HL (Landman‐Parker et al , ; Mauz‐Korholz et al , ; Metzger et al , ; Tebbi et al , ; Wolden et al , ; Keller et al , ) to 77 to 90 % for high risk disease (Schwartz et al , ; Mauz‐Korholz et al , ; Kelly et al , ; Wolden et al , ; Friedman et al , ; Kelly et al , ) in completed trials. With the goal of lowering cumulative doses of anthracyclines to a doxorubicin equivalent dose of ≤250 mg/m 2 and alkylating agents to <7 g/m 2 (cyclophosphamide equivalent dose) (Green et al , ), contemporary paediatric chemotherapy regimens have diverged from the conventional adult approaches of ABVD (adriamycin, bleomycin, vinblastine, dacarbazine) and BEACOPP (bleomycin, etoposide, adriamycin, cyclophosphamide, vincristine, prednisone, procarbazine) by using combination chemotherapy with non‐cross‐resistant agents [adriamycin, bleomycin, vincristine, etoposide, prednisone, cyclophosphamide (ABVE‐PC) or vincristine, etoposide, prednisone, adriamycin/ cyclophosphamide vincristine, prednisone, dacarbazine (OEPA/COPDac)] (Mauz‐Korholz et al , ; Friedman et al , ).…”
Section: Primary Prevention To Close the Survivorship Gapmentioning
confidence: 99%
“…These studies demonstrate anti‐lymphoma efficacy with lower cumulative doses of alkylating agents and anthracyclines (Table ) than are customary with adult treatment regimens (Kelly, ). Furthermore, risk‐based response adapted approaches, facilitated by interim imaging in recent paediatric trials have decreased RT delivery (Friedman et al , ; Keller et al , ; Kelly et al , ).…”
Section: Primary Prevention To Close the Survivorship Gapmentioning
confidence: 99%
“…6,7 For example, current treatment strategies for Hodgkin's lymphoma employ radiation sparingly to minimize the long-term risks of second malignancies and cardiac toxicity even if this increases the risk of recurrence. 6,8,9 Authors of recent and ongoing studies are investigating the impact of reduction of therapy on the incidence of late effects and risk of relapse in other pediatric cancers.…”
mentioning
confidence: 99%